Parietal bone agenesis and athelia in retinoic acid embryopathy: An expansion of the phenotype. Issue 1 (13th November 2021) - Yang, Xiao‐Ru; Wright, James R.; Yu, Weiming; Langdon, Kristopher D.; Somerset, David; Thomas, Mary Ann
Abstract: Background: Retinoic acid signaling plays a critical role during embryogenesis and requires tight regulation. Exposure to exogenous retinoic acid during fetal development is known to have teratogenic effects, producing a recognizable embryopathy. Case: We describe a case of retinoic acid embryopathy secondary to maternal isotretinoin use until the ninth week of gestation and expand the phenotype to include the rare features of parietal bone agenesis and athelia. Histology of the parietal region showed fibrous tissue with no intramembranous ossification. The fetus also had multiple craniofacial dysmorphisms, thymic agenesis, and transposition of the great arteries with double outlet right ventricle and subaortic perimembranous ventricular septal defect. Neuropathology revealed enlarged ventricles with agenesis of the cerebellar vermis, focal duplication of the central canal and scattered parenchymal ependymal rests, and possible cerebral heterotopias with associated abnormal neuronal lamination. A chromosomal microarray was normal. Conclusion: Parietal bone agenesis and athelia are both rare congenital anomalies not previously reported in retinoic acid embryopathy. However, retinoic acid or its degrading enzyme has been demonstrated to exert effects in both of these developmental pathways, offering biological plausibility. We propose that this case may represent an expansion of the phenotype of retinoic embryopathy.